Pengembangan Sistem Blended-Adaptive Learning Berbasis Google Workspace pada Materi SPLSV dan SPtLSV - Bayani, Alfian; Sunismi, Sunismi; Abidin, Zainal (HISTOGRAM: Jurnal Pendidikan Matematika, 2024)
In the VUCA era, education becomes increasingly crucial in preparing students to face future challenges. Mathematics, as a key subject, plays a vital role in developing critical thinking and problem-solving skills. One challenge for Mathematics teachers is that students in the same class may have varying levels of understanding. Therefore, this research aims to develop and test a blended-adaptive learning system based on Google Workspace as a solution for junior high school mathematics education, with a focus on the topics of SPLSV and SPtLSV. This research utilizes the Research and Development (R&D) methodology with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Implementation was carried out with 7th-grade students, and the evaluation method employed a single independent t-test while measuring effectiveness with the N-Gain formula. The results indicate a probability of effectiveness at 0.39, with positive feedback from students regarding the system, reflecting its potential in enhancing students' understanding of mathematics. This research is expected to contribute addressing challenges in mathematics education in the VUCA era, providing better opportunities for students, and promoting innovation in mathematics education.<span style="font-size: 10.0pt; font-family: 'Times New Roman',serif; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: IN; mso-fareast-language: IN; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN">In the VUCA era, education becomes increasingly crucial in preparing students to face future challenges. Mathematics, as a key subject, plays a vital role in developing critical thinking and problem-solving skills. One challenge for Mathematics teachers is that students in the same class may have varying levels of understanding. Therefore, this research aims to develop and test a blended-adaptive learning system based on Google Workspace as a solution for junior high school mathematics education, with a focus on the topics of SPLSV and SPtLSV. This research utilizes the Research and Development (R&D) methodology with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Implementation was carried out with 7th-grade students, and the evaluation method employed a single independent t-test while measuring effectiveness with the N-Gain formula. The results indicate a probability of effectiveness at 0.39, with positive feedback from students regarding the system, reflecting its potential in enhancing students' understanding of mathematics. This research is expected to contribute addressing challenges in mathematics education in the VUCA era, providing better opportunities for students, and promoting innovation in mathematics education.